The sedimentology of the Late Pleistocene Bannow Till stratotype, County Wexford, southeast Ireland. - Evans, D .J. A.; O' Cofaigh, C. (Proceedings of the Geologists' Association, 2008)
The sedimentology and structural features of the Bannow Till are presented from two sites in Bannow Bay, CountyWexford, southern Ireland, the stratotype for this Irish inland till. Beach deposits of last interglacial age are overlain locally by aeolian sands, providing a maximum age for the deposition of the Bannow Till. Three sedimentary units at Bannow comprise a vertical continuum of sheared bedrock (glacitectonite) grading upwards into a subglacial till of mostly local derivation. Shearing and clast macrofabric data indicate that ice flow was from the north to northeast, indicative of glacier movement from an inland source. At Wood Village, glacier advance from the northeast is recorded by the glacitectonization of bedrock, interglacial marine sands, aeolian sands and periglacial slope deposits. This glacitectonized sequence of sediments is overlain unconformably by an extensive tabular unit of interbedded diamictons and stratified sediments typical of deposition in proximal proglacial outwash fans. The Bannow Till is classified as a glacitectonite–subglacial traction till continuum, having been derived from the shearing and fragmentation of shale bedrock from which blocks and slabs have been displaced along fault planes by brittle deformation and then edge-rounded and pulverized. The stratigraphic nature of the evidence for glaciation at Bannow Bay, and hence the Bannow Till stratotype, is typical of glacier/ice-sheet marginal settings in areas of soft bedrock.